2019
DOI: 10.1111/cob.12316
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in older adults: Effect of degree of weight loss on cardiovascular markers and medications

Abstract: Summary Obesity worsens the age‐related tendency towards cardiovascular disease and diabetes. Older adults are vulnerable to medication adverse effects. Intentional weight loss in older adults with obesity has been shown to improve cardiovascular and glycaemic markers. The effect of rapid weight loss induced by very‐low‐calorie diets (VLCDs) on these markers has not been evaluated in this group. In this 12‐week study, participants were randomized to one of healthy eating, hypocaloric diet or VLCD, all combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In a recent systematic review, Haywood and Sumithran [52] included RCTs published until January 2018 examining the effects of any type of WL-intervention tested in persons aged 60 years and beyond with obesity (BMI ≥ 30 kg/ m 2 ). They identified two new small trials [53][54][55] actually testing VLCDs with an energy intake around 800-1000 kcal/d through meal replacements (Optifast program) over a relatively short period of time (3-6 months) in older adults without functional impairment or frailty at baseline (age range 65-85 years). One of them was partly industry-funded by Nestlé [53].…”
Section: Potential Benefits and Harms Of Weight Loss In Older Personsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent systematic review, Haywood and Sumithran [52] included RCTs published until January 2018 examining the effects of any type of WL-intervention tested in persons aged 60 years and beyond with obesity (BMI ≥ 30 kg/ m 2 ). They identified two new small trials [53][54][55] actually testing VLCDs with an energy intake around 800-1000 kcal/d through meal replacements (Optifast program) over a relatively short period of time (3-6 months) in older adults without functional impairment or frailty at baseline (age range 65-85 years). One of them was partly industry-funded by Nestlé [53].…”
Section: Potential Benefits and Harms Of Weight Loss In Older Personsmentioning
confidence: 99%
“…In both trials WL was greatest in the VLCD group, with comparable differences in the reduction of FM and WC. Haywood and colleagues in their trial also analysed changes in biomarkers of cardiovascular risk and found that improvements were more pronounced in the VLCD group [55]. However, the loss of LM and BMD was also greater in the VLCD group [54].…”
Section: Potential Benefits and Harms Of Weight Loss In Older Personsmentioning
confidence: 99%
“…Each disease is accompanied by weight loss. (13,55) Weight loss helps to recover. Simple restriction of food intake decreases MR by 45%.…”
Section: Individual Bodyweight Potential Body Energy Lifespanmentioning
confidence: 99%
“…Weightloss recovers from a lot of chronic diseases such as hypertension, gastric ulcer, psoriasis, diabetes, bronchial asthma, neoplasms, urolithiasis, gallstone disease, and etc. (13,(58)(59)(60)(61) Overeating at overweight deteriorates digestive; leads to malnutrition, metabolic intoxication, and immune stress. (62) Alimentary energy is energy expenditure for food intake, digestive, absorption, transport, storage, and eliminating.…”
Section: Individual Bodyweight Potential Body Energy Lifespanmentioning
confidence: 99%
See 1 more Smart Citation